2014
DOI: 10.4267/2042/53491
|View full text |Cite
|
Sign up to set email alerts
|

Insight in inflammation and cancer

Abstract: This work is licensed under a Creative Commons Attribution-Noncommercial-No Derivative Works 2.0 France Licence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The study clearly showed higher rate of prostate cancer in West Africa. Clearly, the authors' report opens a new perspective for investigation into problems of prostate cancer burden within the sub-Saharan Africa, from the angle of the cause or the source, and moving away from the most traditional reports of genetic basis of prostate carcinogenesis [ 1 , 7 ] to a possibility of inflammation-mediated prostate carcinogenesis [ 8 , 9 ]. In addition, abundant evidence suggests a potential and important influence of environmental factors acting on prostate cancer risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study clearly showed higher rate of prostate cancer in West Africa. Clearly, the authors' report opens a new perspective for investigation into problems of prostate cancer burden within the sub-Saharan Africa, from the angle of the cause or the source, and moving away from the most traditional reports of genetic basis of prostate carcinogenesis [ 1 , 7 ] to a possibility of inflammation-mediated prostate carcinogenesis [ 8 , 9 ]. In addition, abundant evidence suggests a potential and important influence of environmental factors acting on prostate cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Complete understanding of the causes of prostate cancer remains elusive [ 8 , 10 , 11 ]. We have shown that inflammation of the prostate might increase the risk of developing prostate cancer [ 8 , 9 ]. Importantly, data from the Laboratory of the authors clearly suggest that lack of access to antibiotics and presence of chronic inflammatory molecules might be associated with prostate cancer risk.…”
Section: Introductionmentioning
confidence: 99%